Identification of ARF transcription factor gene family and its defense responses to bacterial infection and salicylic acid treatment in sugarcane - Lin, Jia-Xin; Ali, Ahmad; Chu, Na; Fu, Hua-Ying; Huang, Mei-Ting; Mbuya, Sylvain Ntambo; Gao, San-Ji; Zhang, Hui-Li (Frontiers in Microbiology, 2023)
Auxin response factor (ARF) is a critical regulator in the auxin signaling pathway, involved in a variety of plant biological processes. Here, gene members of 24 SpapARFs and 39 SpnpARFs were identified in two genomes of Saccharum spontaneum clones AP85-441 and Np-X, respectively. Phylogenetic analysis showed that all ARF genes were clustered into four clades, which is identical to those ARF genes in maize (Zea mays) and sorghum (Sorghum bicolor). The gene structure and domain composition of this ARF family are conserved to a large degree across plant species. The SpapARF and SpnpARF genes were unevenly distributed on chromosomes 1–8 and 1–10 in the two genomes of AP85-441 and Np-X, respectively. Segmental duplication events may also contribute to this gene family expansion in S. spontaneum. The post-transcriptional regulation of ARF genes likely involves sugarcane against various stressors through a miRNA-medicated pathway. Expression levels of six representative ShARF genes were analyzed by qRT-PCR assays on two sugarcane cultivars [LCP85-384 (resistant to leaf scald) and ROC20 (susceptible to leaf scald)] triggered by Acidovorax avenae subsp. avenae (Aaa) and Xanthomonas albilineans (Xa) infections and salicylic acid (SA) treatment. ShARF04 functioned as a positive regulator under Xa and Aaa stress, whereas it was a negative regulator under SA treatment. ShARF07/17 genes played positive roles against both pathogenic bacteria and SA stresses. Additionally, ShARF22 was negatively modulated by Xa and Aaa stimuli in both cultivars, particularly LCP85-384. These findings imply that sugarcane ARFs exhibit functional redundancy and divergence against stressful conditions. This work lays the foundation for further research on ARF gene functions in sugarcane against diverse environmental stressors.